Preparation and application of terpyridyl iron coordination polymer based on anthraquinone bridging
By designing a trippyridine iron coordination polymer based on anthraquinone bridge, the problem of insufficient response speed and cyclic stability of existing electrochromic materials is solved, and high optical contrast, fast response speed and good cyclic stability are achieved. electrochromic materials have wide application potential.
Patent Information
- Application Number
- CN202311047453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
Existing electrochromic materials have shortcomings in response speed and cycle stability, and it is difficult to meet the high-performance needs of smart glass and anti-glare automotive rearview mirrors.
A trippyridine iron coordination polymer based on anthraquinone bridge was designed and synthesized, and electrochromic materials with high optical contrast, fast response speed and good cycle stability were prepared through simple synthesis routes and mild conditions.
Devices that exhibit electrochromic function under applied voltage have high optical contrast, fast response speed and good cycle stability, and have potential application value.
Smart Images

Figure CN119490667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic photoelectric functional materials, and specifically relates to the preparation and application of an anthraquinone-bridged terpyridine-iron coordination polymer. Background Art
[0002] Electrochromic materials refer to the phenomenon that materials change their optical properties in response to external electrical stimulation, and can reversibly switch between different redox states. This kind of material is widely used in smart glass, anti-glare car rearview mirrors, smart filters, electrochromic display screens, military camouflage, thermal control and other fields due to its unique photoelectric response characteristics. At present, there are many kinds of electrochromic materials, among which transition metal coordination polymers have the advantages of both organic and inorganic materials, so they have received widespread attention and become a hot spot for research. Among the many transition metal ions, divalent iron ions have the characteristics of low cost, good redox activity, and easy coordination with terpyridine, making iron ions a hot spot for research on metal coordination polymer materials.
[0003] Anthraquinone and its derivatives have excellent electrochromic properties. Therefore, introducing them into terpyridine structural units plays a very important role in optimizing electronic structure, improving film-forming properties, adjusting spectral absorption properties, improving electrochromic optical contrast, accelerating response rate, and improving coloring efficiency and cycle stability. Summary of the invention
[0004] The present invention designs and synthesizes a terpyridine iron coordination polymer based on anthraquinone bridging. The electrochromic material of the present invention has a simple synthesis route, mild conditions and low cost. The device prepared by the terpyridine iron coordination polymer based on anthraquinone bridging designed by the present invention exhibits electrochromic function under applied voltage, and has high optical contrast, fast response speed and good cycle stability, and has potential application value.
[0005] The present invention provides a terpyridine iron coordination polymer material based on anthraquinone bridging, and its chemical structural formula (I) is:
[0006] The synthesis method of the anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY comprises the following steps: 2,6-dibromoanthraquinone is reacted with 3-n-hexylthiophene-2-borate to prepare an intermediate 1, which is then subjected to a bromination reaction with N-bromosuccinimide to generate an intermediate 2, which is then subjected to a Suzuki coupling reaction with terpyridine boronic acid to generate a product AQTH-TPY, and finally subjected to coordination polymerization with FeBF4·6H2O to obtain a final product PAQTH-TPY.
[0007] (1) 2,6-dibromoanthraquinone (5 g, 13.66 mmol), 3-n-hexylthiophene-2-boronate (10.01 g, 40.98 mmol), sodium carbonate (8.69 g, 81.96 mmol), tetrakis(triphenylphosphine)palladium (1.58 g, 1.366 mmol) were added to a 250 mL reaction bottle in sequence, and then 100 mL of toluene, 20 mL of distilled water and 10 mL of water were added. The reaction was evacuated and filled with nitrogen. Under nitrogen protection, the reaction temperature was 90°C and refluxed for 24 h. After the reaction was completed, the mixed solvent was dried by rotating the plate, water was added to the residue, and dichloromethane was extracted. The residue was washed with saturated brine, and the organic phase was collected. After drying with anhydrous sodium sulfate, the organic solvent was removed under reduced pressure. The obtained solid was separated and purified, and vacuum dried to obtain intermediate 1.
[0008] (2) Intermediate 1 (1 g, 1.85 mmol) and N-bromosuccinimide (NBS) (691.53 mg, 3.885 mmol) were dissolved in 30 mL of DCM solution and reacted at room temperature for 12 h. After the reaction was completed, the solvent was dried by spin drying, and then extracted and filtered to obtain intermediate 2.
[0009] (3) The intermediate 2 (200 mg, 0.288 mmol), terpyridine boronic acid (406 mg, 1.152 mmol), potassium carbonate (318 mg, 2.304 mmol), and tetrakis(triphenylphosphine)palladium (33.2 mg, 0.0288 mmol) were added to a 100 mL reaction bottle in sequence, and then 40 mL of DMF solvent was added. The reaction was evacuated and filled with nitrogen. The reaction temperature was 100 ° C. and refluxed for 24 hours. After the reaction was completed, extraction was performed, and finally AQTH-TPY was purified by column chromatography.
[0010] (4) AQTH-TPY and FeBF4·6H2O were dissolved in a mixed solvent of CH2Cl2 / MeOH under nitrogen protection, the reaction temperature was 60°C, and refluxed for 12 hours. After the reaction was completed, the reaction mixture was cooled to room temperature, filtered, and the filter cake was washed with H2O, EtOH, and CH2Cl2 in sequence to obtain PAQTH-TPY.
[0011] The synthesis process is:
[0012]
[0013] In step (1), the molar ratio of 2,6-dibromoanthraquinone, 3-n-hexylthiophene-2-borate, sodium carbonate and tetrakis(triphenylphosphine)palladium is 1:3:6:0.1, the reaction temperature is 90-100° C., and the reaction time is 20-24 hours.
[0014] In step (2), the molar ratio of intermediate 1 to N-bromosuccinimide is 1:2.1, and the reaction is carried out at room temperature for 10-12 hours.
[0015] In step (3), the molar ratio of intermediate 2, terpyridine boronic acid, potassium carbonate and tetrakis(triphenylphosphine)palladium is 16:8:0.1, the reaction temperature is 90-95° C., and the reaction time is 20-24 h.
[0016] In step (4), the molar ratio of AQTH-TPY to FeBF4·6H2O is 1:1.2, the reaction temperature is 60-70°C, and the reaction time is 10-12h.
[0017] The anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY prepared in the present invention is applied to the preparation of a device. The device is composed of a transparent conductive substrate, an electrochromic layer, an electrolyte and a metal electrode, and the specific preparation steps are as follows:
[0018] (1) cutting the transparent conductive substrate into suitable sizes, ultrasonically cleaning the cut conductive substrate in a solvent, and then subjecting the substrate to ultraviolet ozone treatment;
[0019] (2) Take a clean transparent conductive substrate, place it on a spin coater with the conductive surface facing up. Use a pipette to take 20 μL of the N,N-dimethylformamide solution of the iron coordination polymer on the transparent conductive substrate, adjust the speed to 1000 r / min, and continue to spin coat on the spin coater for 120 seconds. After the spin coating is completed, sinter the obtained film on a hot plate at 80°C for 10 minutes, dry to remove excess solvent, and set aside for use.
[0020] (3) The metal electrodes are adhered to both sides of the conductive substrate coated with the electrochromic material by 3M tape, and another transparent conductive substrate is adhered to the electrochromic layer with the metal electrodes, an electrolyte is injected, and then the outer surface is sealed with hot melt adhesive;
[0021] (4) Wrap the conductive tape around the outer ends of the two pieces of conductive glass. 8. The use according to claim 7, characterized in that:
[0022] (1) The transparent conductive substrate is one of ITO conductive glass, FTO conductive glass or a flexible substrate;
[0023] (2) The concentration of the N,N-dimethylformamide solution of the iron coordination polymer is 80 mg / mL;
[0024] (3) The electrolyte is a 3 mol / L aqueous solution of zinc perchlorate, and the metal electrode is zinc;
[0025] The present invention has the following advantages:
[0026] The electrochromic material designed by the present invention has a simple synthesis route, mild conditions and low cost. The device prepared by the anthraquinone-bridged terpyridine iron coordination polymer designed by the present invention exhibits electrochromic function under applied voltage, and has high optical contrast, fast response speed and good cycle stability, and has potential application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The molecular structure of the anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY synthesized in Example 1. DETAILED DESCRIPTION
[0028] Embodiment 1:
[0029] Synthesis of electrochromic material PAQTH-TPY:
[0030]
[0031] (1) 2,6-dibromoanthraquinone (5 g, 13.66 mmol), 3-n-hexylthiophene-2-boronate (10.01 g, 40.98 mmol), sodium carbonate (8.69 g, 81.96 mmol), tetrakis(triphenylphosphine)palladium (1.58 g, 1.366 mmol) were added to a 250 mL reaction bottle in sequence, and then 100 mL of toluene, 20 mL of distilled water and 10 mL of water were added. The reaction was evacuated and filled with nitrogen. Under nitrogen protection, the reaction temperature was 90°C and refluxed for 24 h. After the reaction was completed, the mixed solvent was dried by spin drying, water was added to the residue, and dichloromethane was extracted. The residue was washed with saturated brine, and the organic phase was collected. After drying with anhydrous sodium sulfate, the organic solvent was removed under reduced pressure. The obtained solid was separated and purified, and vacuum dried to obtain intermediate 1 (4.58 g, yield: 62%). 1 H NMR (600MHz, CDCl3) δ8.52 (d, J=2.0Hz, 2H), 8.34 (d, J=8.1Hz, 2H), 7.99 (dd, J=8.1, 2.0Hz, 2H), 7.47 (d, J=1.4Hz, 2H ), 7.07 (q, J=1.1Hz, 2H), 2.68 (t, J=7.8Hz, 4H), 1.73-1.67 (m, 4H), 1.42-1.32 (m, 12H), 0.93 (td, J=5.8, 3.0Hz, 6H).
[0032] (2) Intermediate 1 (1 g, 1.85 mmol) and N-bromosuccinimide (691.53 mg, 3.885 mmol) were dissolved in 30 mL of DCM solution and reacted at room temperature for 12 h. After the reaction was completed, the solvent was dried by spin drying, and then extracted and filtered to obtain intermediate 2 (0.98 g, yield: 76%). 1 H NMR (600MHz, CDCl3) δ8.44 (d, J=2.0Hz, 2H), 8.34 (d, J=8.1Hz, 2H), 7.90 (dd, J=8.1, 2.0Hz, 2H) , 7.32 (s, 2H), 2.66-2.61 (m, 4H), 1.67 (t, J=7.5Hz, 4H), 1.41-1.30 (m, 12H), 0.95-0.91 (m, 6H).
[0033] (3) The intermediate 2 (200 mg, 0.288 mmol), terpyridine boronic acid (406 mg, 1.152 mmol), potassium carbonate (318 mg, 2.304 mmol), and tetrakis(triphenylphosphine)palladium (33.2 mg, 0.0288 mmol) were added to a 100 mL reaction bottle in sequence, and then 40 mL of DMF solvent was added. The reaction was evacuated and filled with nitrogen. The reaction temperature was 100° C. and refluxed for 24 h. After the reaction was completed by spot plate monitoring, extraction was performed, and finally AQTH-TPY (235 mg, yield: 71%) was purified by column chromatography.
[0034] (4) AQTH-TPY and FeBF4·6H2O were dissolved in a mixed solvent of CH2Cl2 / MeOH under nitrogen protection, the reaction temperature was 60°C, and refluxed for 12 hours. After the reaction was completed, the reaction mixture was cooled to room temperature, filtered, and the filter cake was washed with H2O, EtOH, and CH2Cl2 in sequence to obtain the iron coordination polymer PAQTH-TPY.
[0035] Embodiment 2: Preparation and performance testing of electrochromic devices based on anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY:
[0036] (1) Preparation of anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY thin films Cut the 1.5×2.5cm 2ITO (indium tin oxide) conductive glass of different sizes was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 minutes respectively, and then dried with nitrogen. 20 μL of 80 mg / mL N, N-dimethylformamide solution of iron coordination polymer was taken on a conductive glass with a pipette, the speed was adjusted to 1000 r / min, and the spin coating was continued for 120 seconds on the spin coater. After the spin coating was completed, the obtained film was sintered on a hot plate at 80°C for 10 minutes and dried to remove excess solvent.
[0037] (2) Preparation of electrochromic devices
[0038] Use 3M tape to stick metal zinc electrodes on both sides of the spin-coated film. Take another piece of cleaned conductive glass, with the conductive side facing up, and fit it to the film. Inject a 3 mol / L zinc perchlorate aqueous solution into the device as an electrolyte. Use hot melt adhesive to encapsulate the device and stick conductive tape on both ends of the device.
Claims
1. A terpyridine iron coordination polymer based on anthraquinone bridging, characterized in that: It has the chemical structure of formula (I):
2. The method for preparing anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY according to claim 1, characterized in that: The method comprises the following steps: 2,6-dibromoanthraquinone reacts with 3-n-hexylthiophene-2-boric acid ester to prepare intermediate 1, which is then subjected to bromination reaction with N-bromosuccinimide to generate intermediate 2, which is then subjected to Suzuki coupling reaction with terpyridine boronic acid to generate product AQTH-TPY, and finally coordinated with FeBF4·6H2O to obtain polymer PAQTH-TPY; (1) Preparation of intermediate 1: 2,6-dibromoanthraquinone (5 g, 13.66 mmol), 3-n-hexylthiophene-2-borate (10.01 g, 40.98 mmol), sodium carbonate (8.69 g, 81.96 mmol), and tetrakis(triphenylphosphine)palladium (1.58 g, 1.366 mmol) were added to a 250 mL reaction bottle in sequence, and then 100 mL of toluene, 20 mL of distilled water, and 10 mL of water were added. Under nitrogen protection, the reaction temperature was 90° C., and the mixture was refluxed for 24 h. The reaction was observed by spot plate. After the reaction was completed, the mixed solvent was dried by spin drying, water was added to the residue, and the mixture was extracted with dichloromethane. The mixture was then washed with saturated brine, and the organic phase was collected. After drying with anhydrous sodium sulfate, the organic solvent was removed under reduced pressure, and the obtained solid was separated and purified, and dried in vacuo to obtain intermediate 1. (2) Preparation of intermediate 2: Intermediate 1 (1 g, 1.85 mmol) and N-bromosuccinimide (NBS) (691.53 mg, 3.885 mmol) were dissolved in 30 mL of DCM solution and reacted at room temperature for 12 h. After the reaction was completed, the solvent was dried by spin drying, and then extracted and filtered to obtain intermediate 2. (3) Preparation of AQTH-TPY: Intermediate 2 (200 mg, 0.288 mmol), terpyridine boronic acid (406 mg, 1.152 mmol), potassium carbonate (318 mg, 2.304 mmol), and tetrakis(triphenylphosphine)palladium (33.2 mg, 0.0288 mmol) were added into a 100 mL reaction bottle in sequence, and then 40 mL of DMF solvent was added. The reaction was evacuated and filled with nitrogen. The reaction temperature was 100 ° C. and refluxed for 24 h. After the reaction was completed, the plate was monitored, and then extraction was performed. Finally, AQTH-TPY was purified by column chromatography; (4) Preparation of PAQTH-TPY: AQTH-TPY and FeBF4·6H2O were dissolved in a mixed solvent of CH2Cl2 / MeOH under nitrogen protection at a reaction temperature of 60°C and refluxed for 12 h. After the reaction, the reaction mixture was cooled to room temperature and filtered. The filter cake was washed with H2O, EtOH, and CH2Cl2 in sequence to obtain PAQTH-TPY.
3. The method for preparing anthraquinone-bridged terpyridine iron coordination polymer PAQTH-TPY according to claim 2, characterized in that: In the synthesis method, in step (1), the molar ratio of 2,6-dibromoanthraquinone, 3-n-hexylthiophene-2-borate, sodium carbonate and tetrakis(triphenylphosphine)palladium is 1:3:6:0.1, the reaction temperature is 90-100°C, and the reaction time is 20-24h; in step (2), the molar ratio of intermediate 1 and N-bromosuccinimide is 1:2.1, the reaction is carried out at room temperature, and the reaction time is 10-12h; in step (3), the molar ratio of intermediate 2, terpyridine boronic acid, potassium carbonate and tetrakis(triphenylphosphine)palladium is 1:6:8:0.1, the reaction temperature is 90-95°C, and the reaction time is 20-24h; in step (4), the molar ratio of AQTH-TPY and FeBF4·6H2O is 1:1.2, the reaction temperature is 60-70, and the reaction time is 10-12h.
4. Use of an anthraquinone-bridged terpyridine iron coordination polymer as described in the claims as an electrochromic material in an electrochromic device.
5. The use according to claim 4, characterized in that: The electrochromic device is composed of a transparent conductive substrate, an electrochromic layer, an electrolyte and a metal electrode, and the specific steps are: (1) cutting the transparent conductive substrate into a suitable size, ultrasonically cleaning the cut conductive substrate in a solvent, and then subjecting it to ultraviolet ozone treatment; (2) Take a clean transparent conductive substrate, place it on a coating machine with the conductive surface facing up. Use a pipette to take 20 μL of the N, N-dimethylformamide solution of the iron coordination polymer on the transparent conductive substrate, adjust the speed to 1000 r / min, and continue to spin coat on the spin coater for 120 seconds. After the spin coating is completed, sinter the resulting film on an 80°C heating plate for 10 minutes, dry to remove excess solvent, and set aside for use; (3) Use 3M tape to stick the metal electrodes to both sides of the conductive substrate coated with the electrochromic material, then stick another transparent conductive substrate to the electrochromic layer with the metal electrodes, inject electrolyte, and then seal with hot melt adhesive; (4) Wrap the conductive tape around both ends of the device.
6. The use according to claim 5, characterized in that: (1) The transparent conductive substrate is one of ITO conductive glass, FTO conductive glass or a flexible substrate; (2) The concentration of the N,N-dimethylformamide solution of the iron coordination polymer is 80 mg / mL; (3) The electrolyte is a 3 mol / L aqueous solution of zinc perchlorate, and the metal electrode is zinc.
Citation Information
Patent Citations
Preparation method and application of anthraquinone polypyridine ligand and ruthenium-anthraquinone complex
CN103012401A
Terpyridyl transition metal organic polymer and preparation method and application thereof in photocatalytic reduction of carbon dioxide
CN111995761A
Alkyl chain bridged terpyridyl iron coordination polymer electrochromic material
CN112250881A
Electrochromic films prepared by supramolecular self-assembly
WO2010069797A1